MINIMALISIR BIAYA DISTRIBUSI AIR GALON MENGGUNAKAN METODE TRANSPORTASI LEAST COST BERBASIS QM FOR WINDOWS - Khaerunnisa Khaerunnisa; Nurhidayah; Heru Sutejo (CV. ADIBA AISHA AMIRA, 2025)
The distribution of bottled water is an important activity in ensuring the availability of clean water for the community, especially in areas with increasing demand due to population growth. However, this distribution process often faces major obstacles in the form of high operational costs, particularly in small and medium enterprises (SMEs) with limited resources. This study aims to minimise the cost of bottled water distribution by applying the Least Cost Transportation method using the QM For Windows application to the bottled water filling and delivery business owned by Mrs. Nur Linta, located in Kamkey, Abepura. This method was chosen because it provides an optimal solution in determining the most cost-efficient distribution pattern, considering the limitations of delivery capacity and daily customer needs. The data collected includes daily water supply, demand in three target areas (Abe Lingkaran, Kamkey, and Tanah Hitam), and delivery costs per gallon for each distribution route. The analysis results indicate that the application of the Least Cost method yields optimal delivery allocation, with a minimum total cost of 340 (IDR 5,440,000), without compromising service quality or delivery capacity. This study demonstrates that quantitative approaches such as the least cost method can be practically implemented at the SME scale to improve logistics efficiency, reduce operational costs, and support more rational and systematic decision-making in the distribution process